Transforming care: a study on physicians’ awareness, attitudes, and barriers to pressure injury prevention in medical wards in Jordan - Assaf, Enas A.; Alkhresheh, Rahaf; Al Sabbah, Haleama; Al-Akash, Hekmat (Frontiers in Public Health, 2025)
BackgroundPressure injury is a significant global concern, with rising prevalence and substantial direct and indirect costs. A multidisciplinary approach involving nurses and other healthcare team members, particularly physicians, is essential for comprehensively addressing pressure injury (PI) in medical wards. Therefore, this study aims to assess the knowledge, attitudes, and barriers among physicians working in Jordanian general medical wards toward the prevention of pressure injury.MethodA descriptive correlational cross-sectional design was employed, utilizing a convenience sample of 73 physicians from the three largest governmental hospitals in Jordan, representing the country’s most populated regions. A self-administered questionnaire measuring knowledge, attitudes, and barriers was distributed among the study population. Descriptive statistics, including mean (M) and standard deviation (SD), were used to analyze the total scores, while a linear multiple regression model was applied to identify factors influencing knowledge, attitudes, and barriers toward pressure injury prevention in Jordanian medical wards.ResultsThe study found that physicians demonstrated good knowledge but exhibited weak attitudes and recognized significant barriers toward pressure injury prevention. Higher income was associated with significant differences in knowledge and attitude scores (p < 0.00 and p < 0.05, respectively), while the universal guidelines correlated with significant differences in knowledge scores (p < 0.048). Additionally, recognized barriers showed significant differences among those using guidelines and perceived unproportioned staff (p < 0.041, p < 0.03) respectively.ConclusionPhysicians recognized significant barriers that negatively influenced their attitudes toward implementing preventive measures in medical wards. Strengthening the multidisciplinary team approach in medical wards by clarifying roles and responsibilities could enable physicians to more effectively participate in PI prevention efforts.